2019
DOI: 10.1109/tcomm.2019.2907943
|View full text |Cite
|
Sign up to set email alerts
|

Data-Aided Secure Massive MIMO Transmission Under the Pilot Contamination Attack

Abstract: In this paper, we study the design of secure communication for time division duplex multi-cell multi-user massive multiple-input multiple-output (MIMO) systems with active eavesdropping. We assume that the eavesdropper actively attacks the uplink pilot transmission and the uplink data transmission before eavesdropping the downlink data transmission of the users. We exploit both the received pilots and the received data signals for uplink channel estimation. We show analytically that when the number of transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…• Pilot sequence [61]: The eavesdropper sends the same pilot sequence as that of the targeted device. This way may degrade the secrecy performance more severely.…”
Section: Activity Detection and Channel Estimationmentioning
confidence: 99%
“…• Pilot sequence [61]: The eavesdropper sends the same pilot sequence as that of the targeted device. This way may degrade the secrecy performance more severely.…”
Section: Activity Detection and Channel Estimationmentioning
confidence: 99%
“…In [29], a secure communication for time-division duplex multi-cell multi-user massive MIMO systems was investigated when an active eavesdropping performs PCAs. Therein, it was shown that decreasing the desired user's signal power can be beneficial to combat a strong active attack from an eavesdropper.…”
Section: Impact Of Channel State Informationmentioning
confidence: 99%
“…Note that the proposed signal extraction depends on the minimum of L {F {uY}}, where L {F {uY}} remains unchanged when the angles of its input are rotated. On the other hand, optimization problem (8) just indicates that the extracted signal belongs to one user, but it cannot determine which user corresponds to the extracted signal. Thus, order ambiguity also exists.…”
Section: Channel Identificationmentioning
confidence: 99%
“…The normalized mean square error (NMSE) of the channel estimation and the bit error rate (BER) of separation signal are also selected as a performance metric. We simulate and compare the performance of our proposed method in this paper, the bounded component analysis (BCA) method [14] and the eigenvalue decomposition (EVD)-based method [8]. Also, we simulate the performance that achieved under perfect CSI.…”
Section: Channel Identificationmentioning
confidence: 99%